Chemically grown Bi2S3 nanorod films for hydrogen evolution. (8th September 2022) - Chalapathi, U.; Reddy, B. Purushotham; Sreekanth, T.V.M.; Park, Si-Hyun
Abstract: Bi2 S3 nanorod films were grown on ITO-coated glass substrates through chemical bath deposition (CBD) and annealing in a sulfur atmosphere. The as-deposited films were amorphous/nanocrystalline, with a particle size of 20 nm and a direct optical band gap of 1.87 eV. Upon annealing at 350 °C, the films exhibited a nanorod morphology with a length of 300 nm. Further increasing the temperature from 400 to 450 °C resulted in an increased diameter of nanorods. The direct optical band gap decreased from 1.68 to 1.47 eV upon increasing the annealing temperature from 350 to 400 °C. Photoelectrochemical (PEC) measurements showed that the nanorod films grown on ITO-coated glass substrates exhibited significantly increased PEC activity owing to their nanorod structures. The Bi2 S3 nanorod films formed at 400 °C exhibited a maximum photocurrent density of 6.1 mA/cm 2 at 1 V, which was 2.5 times higher than that of the as-deposited films. The enhancement in the photocurrent density could be due to the effective visible-light absorption of Bi2 S3 nanorods as a result of the increased crystallinity and decreased band gap. This study demonstrates the synthesis route involving a simple and inexpensive CBD method of Bi2 S3 nanorod films for the optimized PEC water-splitting applications. Highlights: Growth of Bi2 S3 nanorod films on ITO-coated substrates by CBD and annealing. Effect of annealing temperature on Bi2 S3 nanorod formation was investigated. The bandgap of Bi2 S3 decreased from 1.68 to 1.47 eV upon increasing annealing temperature. The prepared Bi2 S3 nanorod films exhibited significant increase in the PEC activity. Bi2 S3 nanorod films formed at 400 °C exhibited a maximum photocurrent density of 6.1 mA/cm 2 at 1 V vs. Hg/HgO.